Risk Factors For Progression From Biochemical Leak to Clinically Relevant Postoperative Pancreatic Fistula After Pancreaticoduodenectomy. The Key of the Lock: Prognostic Nutritional Index - Mehmet Can Aydin; Oguzhan Ozsay; Kagan Karabulut; Recep Bircan; Fatih Atalay; Mehmet Batuhan Ors (The Turkish Journal of Gastroenterology)
Background/Aims: Postoperative pancreatic fistula (POPF), which is considered the most frightening complication after pancreatic oduodenectomy (PD), continues to be a serious problem even in experienced centers. In the present study, we aimed to determine the risk factors that increase the progression from biochemical leak (BL) to clinically relevant postoperative pancreatic fistula (CR-POPF) after PD.